Dental anomalies in syndromes displaying hypertrichosis in the clinical spectrum - Vinícius Figueiredo CARNEIRO; Renato Assis MACHADO; Mauro Costa BARBOSA; Verônica Oliveira DIAS; Daniella Reis Barbosa MARTELLI; Hercílio MARTELLI-JÚNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Hypertrichosis and dental anomalies may occur alone or in combination in the spectrum of many syndromes. To identify genetic entities characterized by hypertrichosis and dental anomalies, a search was performed in the Mendelian Inheritance in Man database with the terms "hypertrichosis" or "hirsutism" and "tooth" or "dental abnormalities." Nondependent androgen metabolism disturbances were classified as hypertrichosis. Genetic entities with hypertrichosis and dental anomalies were included in the study. Additional searches were performed in the PubMed and Orphanet databases, when necessary, in order to include data from scientific articles. An integrative analysis of the genes associated with the identified syndromes was conducted using STRING to characterize biological processes, pathways, and interactive networks. The p-values were subjected to the false discovery rate for the correction of multiple tests. Thirty-nine syndromes were identified, and dental agenesis was the most frequent dental anomaly present in 41.02% (n = 16) of the syndromes. Causative genes were identified in 33 out of 39 genetic syndromes. Among them, 39 genes were identified, and 38 were analyzed by STRING, which showed 148 biological processes and three pathways that were statistically significant. The most significant biological processes were the disassembly of the nucleosome (GO:0006337, p = 1.09e-06), chromosomal organization (GO:0051276, p = 1.09e-06) and remodeling of the chromatin (GO: 0006338, p = 7.86e-06), and the pathways were hepatocellular carcinoma (hsa05225, p = 5.77e-05), thermogenesis (hsa04714, p = 0.00019), and cell cycle (hsa04110, p = 0.0433). Our results showed that the identification of hypertrichosis and dental anomalies may raise the suspicion of one of the thirty-nine syndromes with both phenotypes.